Protected areas have remarkable spillover effects on forest conservation on the Qinghai‐Tibet Plateau. (31st December 2021) - Shen, Yu; Liu, Guohua; Zhou, Wei; Liu, Yuqing; Cheng, Hao; Su, Xukun
Abstract: Aim: Although protected areas (PAs) are assumed to reduce natural threats within boundaries, their spillover effects remain equivocal. It is necessary to determine whether PAs truly achieve conservation targets and whether they promote or inhibit natural habitat degradation in adjacent areas by blockage or leakage spillover. This study aims to choose 54 nature reserves (NRs) focusing on forest protection as a case study to assess PA conservation effectiveness and spillover prevalence. Location: PAs on the Qinghai‐Tibet Plateau (QTP). Methods: We used matching methods to compare deforestation rates inside PAs and their 20 km buffer zones with matched control areas based on the Global Forest Change dataset from 2001 to 2019. We contrasted the effects of NRs with different management levels, ages and areas. We designed five concentric buffer zones to assess spillover change with distance and estimated potential drivers of the spillover effect to explain its directions and magnitudes. Results: 75.9% of the NRs were effective in preventing deforestation within their boundaries. NRs with different properties showed similar performance on forest conservation. Spillover effects were heterogeneous around NRs. One hundred and twenty‐two buffer zones had positive spillover ranging from 0.1% to 5.3%. One hundred and nineteen buffer zones had leakages from −8.84% to −0.1%. Blockages slightly outnumbered leakages at different distances, while leakages happened more frequently when we treated buffer zones as a whole spillover area. The linear model indicated NR age and population density of buffer zones were the most relevant predictors to spillover value. Main conclusions: Most PAs performed well in forest conservation. Leakages could undermine or offset PA conservation efforts and were related to multiple natural or socio‐economic factors. We recommend considering the plurality of PAs as well as spillover effect and incorporating a social‐ecological framework in further PA establishment and management.